Mechanism for transforming the competitive potential of tourism industry subjects in the post-war period - Kovalska, Liubov; Ierko, Iryna; Barskyi, Yurii (Економічний форум, 2024)
The relevance of the research concerns the implementation of the mechanism for transforming the competitive potential of tourism industry entities in the post-war period to ensure market balance, stability, and competitiveness. Martial law conditions limit the capacities of the industry subjects to implement the concept of competitiveness transformation, which can lead to an imbalance in the tourism services market due to the lack of effective management. The purpose of the study was to develop a mechanism for transforming the competitive potential of tourism industry entities. The study employed both general scientific and special methods of research: methods of analysis and synthesis, method of generalisation, methods of analysis of facts, methods of system-functional approach, and method of systematisation. The essence of the transformation mechanism, presented in three blocks, is substantiated. The basis of the 1st block is a specification of the concept formation according to various scenarios, determination of goals, and institutionalisation. The purpose of the 2nd block is to determine the phases (turbulence, fluctuation, bifurcation, deformation, and transformation) of the transformation by the criteria (sustainability, safety, and competitiveness). The determinant feature of the 3rd block is the tools and means of implementing the transformation mechanism (support systems, development strategy, methods of implementation). The study highlights a differentiated approach to the selection of transformation goals. The institutionalisation in this study is interpreted as a set of institutes and institutions, owing to which transformative processes can ensure the sustainability, safety, and competitiveness of the tourism industry. The legal, organisational, information, and marketing subsystems, which act as supporting subsystems, are analysed. The study focuses on such tools for the implementation of the transformation mechanism as marketing (ensuring tourists’ satisfaction with the quality of tourist services), fiscal policy (regulation of costs and income), and reproduction (creation of new competitive advantages, restoration of tourist potential). The study elucidates the role of methods of implementing the mechanism for transforming the competitive potential of tourism industry subjects (planning, forecasting, and pricing), different intensities of influence, features of their manifestation, and time/periods of external and internal factors influence. The proposed mechanism is of great practical importance. The application of a differentiated approach to transformation processes will help to balance demand and supply in the market of tourist services